1998
DOI: 10.1128/mcb.18.10.6023
|View full text |Cite
|
Sign up to set email alerts
|

A Positive GATA Element and a Negative Vitamin D Receptor-Like Element Control Atrial Chamber-Specific Expression of a Slow Myosin Heavy-Chain Gene during Cardiac Morphogenesis

Abstract: We have used the slow myosin heavy chain (MyHC) 3 gene to study the molecular mechanisms that control atrial chamber-specific gene expression. Initially, slow MyHC 3 is uniformly expressed throughout the tubular heart of the quail embryo. As cardiac development proceeds, an anterior-posterior gradient of slow MyHC 3 expression develops, culminating in atrial chamber-restricted expression of this gene following chamberization. Two cis elements within the slow MyHC 3 gene promoter, a GATA-binding motif and a vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
18

Year Published

2000
2000
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(82 citation statements)
references
References 68 publications
1
54
0
18
Order By: Relevance
“…These effects on myosin gene expression might partially underlie the associations of vitamin D status and myocardial contractility, which have been observed in rodents [45][46][47].…”
Section: Other Molecular Effects Of Vitamin D On the Myocardiummentioning
confidence: 91%
See 1 more Smart Citation
“…These effects on myosin gene expression might partially underlie the associations of vitamin D status and myocardial contractility, which have been observed in rodents [45][46][47].…”
Section: Other Molecular Effects Of Vitamin D On the Myocardiummentioning
confidence: 91%
“…Expression of myosin, a major contractile protein of the myocardium, is also regulated by vitamin D [45][46][47]. These effects on myosin gene expression might partially underlie the associations of vitamin D status and myocardial contractility, which have been observed in rodents [45][46][47].…”
Section: Other Molecular Effects Of Vitamin D On the Myocardiummentioning
confidence: 98%
“…It has been shown previously that GATA-4 regulates the expression of many contractile proteins, such as ␣-myosin heavy-chain, ␤-myosin heavy-chain, and cardiac troponin I in cardiomyocytes ) and activates the promoter of several contractile protein genes, such as cardiac troponin C, slow myosin heavy-chain, and cardiac ␣-actin, alone or in combination with other transcription factors (Ip et al 1994;Molkentin et al 1994;Murphy et al 1997;Sepulveda et al 1998;G.F. Wang et al 1998;Morin et al 2000).…”
Section: Gata-4 Is Essential For Cardiomyocyte Sarcomere Reorganizationmentioning
confidence: 99%
“…Since knockout mice exhibited specification of the cardiac cell lineage, 3,4) and ES cells with homozygous GATA-4(Ϫ/Ϫ) contributed to the heart tissue in chimeric embryos, 3) GATA-4 in procardiomyocytes or visceral endoderm cells likely regulate the expression of a morphogenic signaling molecule(s) that directs the migration of procardiomyocytes. Although GATA-4 knockout mice express cardiac contractile proteins, 3,4) a number of studies have suggested that both structural and regulatory genes in the cardiac muscle cells are targets of GATA-4, such as those of A1 adenosine receptor, 5) angiotensin II type Ia receptor, 6) atrial natriuretic peptide, 7) brain natriuretic peptide, [7][8][9] cardiac a actin, 10) cardiac troponin C, 11) cardiac troponin I, 9) cardiac-restricted ankyrin repeat protein, 12) amyosin heavy-chain, 9,13) b-myosin heavy-chain, 9) myosin light chain 1/3, 14) Na ϩ /Ca 2ϩ exchanger 1, 15,16) Nkx-2.5, 17,18) slow myosin heavy chain, 19) and corin. 20) It is also evident that GATA-4 functions in the regulation of both epithelial cell differentiation and gene expression in the gut 21,22) and gonads [23][24][25][26][27] in addition to the heart.…”
mentioning
confidence: 99%